AN EVALUATION OF SOCIAL MEDIA AS STRATEGY FOR ENHANCING COMPETITIVENESS AMONG SELECTED SMALL MEDIUM ENTERPRISES IN NAIROBI COUNTY, KENYA - Gitau, Peris; Munyau, Joseph; Waweru, Jimnah (European Journal of Business and Strategic Management, 2017)
Purpose: To evaluate how social media can be used as a strategy that enhances competitiveness among the SMEs. Methodology: The study adopted a descriptive research design. Findings: The study results revealed that the social media platforms mentioned were namely, facebook, twitter, my space, website, flicker, tumblr, instagram, linkedin, stumble upon, whatapp, skype and blogger. Results also showed that the respondents' frequency of use of facebook, twitter, website, tumblr, linkedin and whatapp was high. Results indicated that the purpose for use using social media was to access customers and suppliers and to advertise products, to buy and sell online, to connect with suppliers, to manage customer relationships and to research on market competition and opportunities. Further, results revealed that adoption of social media has assisted their business to; access more customers, generate more profits, increase the sales, reduce the operational costs, increased customer relationship, increased efficiency and increased ability to tell on customer needs. The chi square results indicated that adoption of social media influenced organization competitiveness positively. Results also indicated that the respondents faced the challenge of lack of necessary skills, lack of a computer or phone, lack of internet connectivity, lack of finances and hacking of user accounts. Unique contribution to theory, practice and policy: The findings of this study are important to the existing SME's, those who have physical premises and those who are yet to begin the business, because they will be provided for with information that will be used in future decision making. Adopt social media as a strategy that will impact the business competition. The findings of the study will also add value to the research and development department since they will know how to advice the strategy and design group on how to achieve a digital plat form without fail. The study will have a major significance in the Kenya government especially, devolution ministry, and the vision 2030 docket since it aims at development of information technology and advancement. The study will be used by financial institutions when advancing the customers on how to set up a business and how to reduce the cost.